Aromatic Sulfoxide and Sulfone Warheads - Reactivity and Stability Data - Nyström, Hampus; Valaka, Anna P.; Grøtli, Morten (University of Gothenburg, 2026)
HPLC chromatograms used for determining stability half-lives (t₁/₂) in PBS buffer and reactivity
half-lives (t₁/₂) with N-acetyl cysteine (NAC) of tested aromatic sulfoxide and sulfone warhead fragments.

HPLC-kromatogram som har använts för att bestämma stabilitetshalveringstider (t₁/₂) i PBS-buffert samt reaktivitetshalveringstider (t₁/₂) med N-acetylcystein (NAC) för testade aromatiska sulfoxid- och sulfon-warheadfragment.
Aromatic Sulfoxide and Sulfone Warheads - Reactivity and Stability Data
Keywords: organic chemistry; organisk kemi; buffers (chemistry); covalent bonds; cysteine; nucleophiles; reactivity; sulfones; warheads; Organic Chemistry; Organisk kemi; Medicinal Chemistry; Läkemedelskemi